Pengaruh Kualitas Pelayanan, Pemasaran Syariah Dan Etika Bisnis Syariah Terhadap Keputusan Generasi Milenial Menjadi Nasabah Pada Bank Syariah Di Surabaya - Warni, Fortuna Septiyaning; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2025)
The development of sharia banking has caused the banking industry to become increasingly competitive, namely competition between sharia banking and conventional banking or fellow sharia banks to gain respective profits. Currently, the millennial generation is considered as potential consumers for Sharia banking. The millennial generation has the potential to increase economic activity, including the Sharia economy. This research is quantitative with a causal associative approach, and uses a non-probabilistic sampling method. The Structural Equation Model (SEM) analysis technique uses the PLS application. The results of this study show that Islamic marketing and Islamic business ethics influence millennials’ decisions to become customers of Islamic banks. In contrast, service quality does not affect their decision to choose Islamic banks. This means Islamic banks should focus on strategies related to Islamic marketing and the application of Islamic business ethics to attract millennial customers. On the other hand, improving service quality alone is not enough, so banks need to highlight the unique value of sharia principles in their marketing strategies.